Policy harmonisation, regional integration and energy security: the participation of independent power producers in the Sub-Saharan African energy sector - Pailman, Kelsey Amy (Department of Commercial Law, 2020)
The United Nations Sustainable Development Goal Seven (SDG 7) promotes access to 'affordable, reliable, sustainable and modern energy for all’. Sub-Saharan Africa is however characterised by high levels of energy insecurity. Regional integration is a way in which energy security in the region can be achieved through the sharing of resources, infrastructure and expertise. Electricity trade in Sub-Saharan takes place primarily through the Southern African Power Pool. The Power Pool consists of 13 member countries that import and export electricity across transmission infrastructure. Regional integration is however hampered by unreliable state-owned centralised grids. Many grids in sub-Saharan Africa do not have sufficient energy generation capacity for regional trade. Independent Power Producers (IPPs) promote regional integration and energy security by increasing a country’s energy generation capacity and diversifying its energy mix through renewable energy sources. Sub-Saharan Africa currently lacks a harmonised policy framework on the participation of IPPs in national energy markets. This thesis argues that a harmonised policy framework on IPP participation on a national level can increase electricity trade and energy security regionally.